Palliative Care as a Standard of Care in Pediatric Oncology. Issue 5 (23rd December 2015) - Weaver, Meaghann S.; Heinze, Katherine E.; Kelly, Katherine P.; Wiener, Lori; Casey, Robert L.; Bell, Cynthia J.; Wolfe, Joanne; Garee, Amy M.; Watson, Anne; Hinds, Pamela S.
Abstract : The study team conducted a systematic review of pediatric and adolescent palliative cancer care literature from 1995 to 2015 using four databases to inform development of a palliative care psychosocial standard. A total of 209 papers were reviewed with inclusion of 73 papers for final synthesis. Revealed topics of urgent consideration include the following: symptom assessment and intervention, direct patient report, effective communication, and shared decision‐making. Standardization of palliative care assessments and interventions in pediatric oncology has the potential to foster improved quality of care across the cancer trajectory for children and adolescents with cancer and their family members. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.